2011
DOI: 10.4310/ajm.2011.v15.n1.a2
|View full text |Cite
|
Sign up to set email alerts
|

Good Shadows, Dynamics and Convex Hulls of Complete Submanifolds

Abstract: Abstract. Any non-empty open convex subset of R n is the convex hull of a complete submanifold M , of any codimension, but there are obstructions if the geometry of M is, a priori, suitably controlled at infinity. In this paper we develop tools to explore the geometry of ∂[Conv(M )] when the Grassmanian-valued Gauss map of M is uniformly continuous, a condition that, in the C 2 case, is weaker than bounding the second fundamental form of M . Our proofs are based on the Ekeland variational principle, and on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The proof below was inspired by the proof of a conceptual refinement of the OmoriYau maximum principle stated in [7]. P  T 1.2.…”
Section: The Argumentsmentioning
confidence: 99%
“…The proof below was inspired by the proof of a conceptual refinement of the OmoriYau maximum principle stated in [7]. P  T 1.2.…”
Section: The Argumentsmentioning
confidence: 99%
“…In [6] an application of the above lemma was given to the study of the convex hull of complete submanifolds. As a corollary, one obtains the sharp result that the boundary of the convex hull of a compact C 1 hypersurface in R n is itself of class C 1 .…”
Section: Lemma 34 (Theorem 33 In [6]mentioning
confidence: 99%
“…Lemma 3.4 is the first order version of the main result of [6], where it is shown that in the well-known Omori-Yau maximum principle [1], [10], [17], one can find sequences of points resembling local maxima (in terms of properties of the gradient, Hessian and Laplacian) that shadow asymptotically any prescribed maximizing sequence. By way of comparison, the original Omori-Yau maximum principle predicts the existence of some maximizing sequence whose points resemble local maxima.…”
Section: Lemma 34 (Theorem 33 In [6]mentioning
confidence: 99%
“…This principle turned out to be a powerful tool in geometric analysis (see, for instance, [3,5,11,14] for a recent application).…”
Section: Introductionmentioning
confidence: 99%